Short-term outcomes of oropharyngeal administration of colostrum in preterm neonates: a double-blind placebocontrolled randomized trial - Ameneh Lamsehchi; Maryam Shokouhi Solgi; Mohammad Kazem Sabzehei; Behnaz Basiri; Elahe Talebi Ghane; Kiana Kimiaei Asadi; Sina Azadnajafabad (Clinical and Experimental Pediatrics)
Background The oropharyngeal administration of colostrum (OAC) in neonates has several benefits. Purpose To investigate the short-term outcomes of OAC in preterm neonates. Methods We performed this 2-arm, double-blind, placebo-controlled randomized trial at a tertiary neonatal center in Iran in 2021–2023. The intervention and control arms received 0.2 mL of their mother’s colostrum or distilled water via oropharyngeal administration every 6 hours for 3 days starting from birth until 72 hours of age. The main study outcomes were neonatal death, the incidence of necrotizing enterocolitis, sepsis, retinopathy of prematurity (ROP), length of hospital stay, and period to full enteral feeding. A regression analysis was used to adjust for possible confounders. Results A total of 126 neonates (mean gestational age, 30.05 weeks) were randomized to the intervention and placebo groups (n=63 each) and had a mean±standard deviation weight of 1,247±193 g versus 1,156±215 g (P=0.013) and 1- and 5-min Apgar scores of 6.35 versus 5.38 (P=0.003) and 7.84 versus 7.13 (P=0.001), respectively. The mortality rate was 12.7% in the intervention group versus 14.3% in the placebo group (P=0.794). The necrotizing enterocolitis rate was significantly lower in the intervention versus placebo arm (11.1% vs. 28.6%, respectively, P=0.010), as was the clinically suspected sepsis rate (15.9% vs. 39.7%, respectively, P=0.004). The ROP and bronchopulmonary dysplasia rates did not differ significantly between groups after the adjustment for confounders. The mean length of hospital stay was shorter in the intervention group (26.1 days vs. 37.32 days, P=0.023). Moreover, the mean duration of antibiotic therapy and period to full feeding were significantly shorter in the intervention group. Conclusion OAC could effectively decrease the incidence of complications in preterm infants and facilitate earlier patient discharge.